Pemanfaatan Aplikasi Sehat Ibu Dan Anak Melalui Imunisasi (SEHATI) Sebagai Media Digital Pemantauan Kesehatan Ibu dan Anak Di Klinik Bidan Delima Surabaya - Sulaksono, Danang Haryo; Prabiantissa, Citra Nurina; Yuliastuti, Gusti Eka; Hapsari, Dian Puspita (Parta: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity employed a participatory approach through demonstration-based and hands-on training to improve the digital literacy of healthcare workers and the community in using the SEHATI application. The main issue identified at the partner location was that maternal and child health service records were still processed manually, leading to service delays and a higher risk of data loss. The training was attended by five midwives and clinical assistants, along with fifteen community representatives consisting of pregnant women and health cadres. Evaluation results showed an increase in participants’ ability to use the application, with an average improvement of 78% between pre-test and post-test scores. The implementation of SEHATI proved to enhance service efficiency for midwives as providers and facilitated easier access to health information for community members as users. Socially, this activity strengthened digital health literacy and supported the transformation of primary healthcare services toward a more effective and digitized system.